Memaknai Ulang Panca Tugas Pemimpin Menurut 2 Timotius 4:1-5 Sebagai Pedoman Bagi Kepemimpinan Kristen Masa Kini - Etni Grace Andi Yusuf; Suhadi Suhadi; Yonatan Alex Arifianto (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2022)
In this era of disruption in which the world is undergoing massive changes in all fields that change the entire fabric of people's lives, Christian leadership is also experiencing challenges. A Christian leader is also required to be sensitive to the present. A Christian leader must be realistic in facing various challenges. This article will examine what the duties of a church leader are as a responsibility in his leadership to face the challenges of the times in the form of unhealthy teaching that attacks the life of the congregation. The author bases his study on the five duties of a leader in 2 Timothy 4:1-5. The method that the author uses in the presentation of this article is a descriptive qualitative method with a text analysis approach and literature study. Based on biblical analysis, it can be concluded that the five duties of a leader in facing the challenge of unhealthy teachings in the congregation, so that leaders can help the congregation in maintaining their faith in the midst of today's era of disruption.AbstrakDi era disrupsi ini yang mana dunia tengah mengalami perubahan besar-besaran di segala bidang yang merubah seluruh tatanan kehidupan masyarakatnya, kepemimpinan Kristen juga mengalami tantangan. Seorang pemimpin Kristen juga dituntut untuk peka terhadap kekinian. Seorang pemimpin Kristen harus realistis dalam menghadapi berbagai tantangan Artikel ini hendak mengkaji apa tugas pemimpin jemaat sebagai tanggungjawab dalam kepemimpinannya untuk menghadapi tantangan zaman berupa pengajaran tidak sehat yang menyerang masuk dalam kehidupan jemaat. Penulis mendasarkan kajiannya pada lima tugas pemimimpin dalam 2 Timotius 4:1-5. Adapun metode yang penulis gunakan dalam pemaparan artikel ini yaitu metode kualitatif deskriptif dengan pendekatan analisi teks dan studi pustaka. Berdasarkan analisis biblikal maka dapat diperoleh pancatugas seorang pemimpin dalam menghadapi tantangan adanya ajaran yang tidak sehat dalam jemaat, sehingga pemimpin dapat menolong jemaat dalam pemeliharaan iman mereka ditengah-tengah era disrupsi hari ini.